Operative Management of Burns: Traditional Care - David G. Greenhalgh (MDPI AG, 2023)
Surgical treatment of burn wounds has had a tremendous impact on burn patients. The survival of patients with massive burns is now very common. Expeditious coverage of the wound has been a major contributor to improved survival, but survival is not enough. There is a need to improve the ultimate functional and cosmetic outcomes of the wound in order to facilitate a patient's return to society. This paper reviews strategies, using fairly basic techniques, to optimize the outcomes of burn patients. While there are many new skin products available, the strategies presented here can apply to any surgeon treating burns throughout the entire world.